53.9k views
1 vote
(X+4+1)(x+4)=(11+x+1)(x+1) solve for x

1 Answer

1 vote

Answer:

x= 2

Explanation:

so you add the values given in the brackets and leave X as it is (do this on both sides of the equation.

1. (x + 5)(x+4)= (x+12)(x+1)

2. multiply the parenthesis on both sides or one at a time

so,
x^(2)+5x+4x+20 =
x^(2)+12+1x+12

3. cancel like terms which we have
x^(2) so remove that.

5x+4x+20=12+1x+12

4. collect like terms.

9x + 20 = 13x + 12

5. move like terms.

9x-13x=12-20 = -4 = -8

6. x=
(-4)/(-8) divide both sides by 4 or basically simplify 4 divided by 8

which leaves u with

x= 2

hope this helps x, let me know if u have any questions. photomath is an app that helps too.

User Contacto Contact
by
5.7k points